THE EFFECT OF PROFITABILITY, FIRM SIZE AND FINANCIAL LEVERAGE ON INCOME SMOOTHING PRACTICES IN NON-CYCLICALS CONSUMER SECTOR LISTED IDX 2021-2023 - Stella Stella; Elsa Imelda; Emillia Sastrasasmita (Graduate Program of Universitas Tarumanagara, 2025)
The objective of this research is to ascertain how profitability, firm size, financial leverage affect income smoothing. This research utilized a quantitative approach. Purposive sampling was the method chosen and used, then this method produced 73 samples of companies listed on the Indonesia Stock Exchange for 3 periods from 2021-2023. The SPSS application was used to process data and test the hypothesis of logistic regression analysis. Accordings to the findings, income smoothing is significantly positively affected by profitability and financial leverage. On the other hand, income smoothing is unaffected by firm size.